1997
DOI: 10.1161/01.cir.95.9.2277
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic Ventricular Fibrillation Induced With Vagal Activity in Patients Without Obvious Heart Disease

Abstract: We propose this VF associated with late r'/ST elevation in the precordial leads and influenced by vagal activity as a new possible mechanism of idiopathic VF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
285
4
3

Year Published

2005
2005
2006
2006

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 369 publications
(309 citation statements)
references
References 15 publications
17
285
4
3
Order By: Relevance
“…A circadian variation of fluctuation in ST elevation was also demonstrated 8,11 and ST elevation always became prominent just before VF episodes. 8 We recently reported a dynamic, circadian change in ST elevation during daily life of BS patients by means of a unipolar lead Holter ECG. 11 In that study, an increase in vagal activity occurred together with a spontaneous augmentation of ST elevation.…”
Section: Circulation Journal Vol70 July 2006mentioning
confidence: 79%
See 4 more Smart Citations
“…A circadian variation of fluctuation in ST elevation was also demonstrated 8,11 and ST elevation always became prominent just before VF episodes. 8 We recently reported a dynamic, circadian change in ST elevation during daily life of BS patients by means of a unipolar lead Holter ECG. 11 In that study, an increase in vagal activity occurred together with a spontaneous augmentation of ST elevation.…”
Section: Circulation Journal Vol70 July 2006mentioning
confidence: 79%
“…[7][8][9]13,14 Several studies have demonstrated that the ECG in patients with BS changes dynamically. 8,9,11,13 The configuration and degree of ST-segment elevation in the precordial leads change from day to day. A circadian variation of fluctuation in ST elevation was also demonstrated 8,11 and ST elevation always became prominent just before VF episodes.…”
Section: Circulation Journal Vol70 July 2006mentioning
confidence: 99%
See 3 more Smart Citations